A Regression Model to Predict Linezolid Induced Thrombocytopenia in Neonatal Sepsis Patients: A Ten-Year Retrospective Cohort Study - Duan, Lufen; Zhou, Qin; Feng, Zongtai; Zhu, Chenqi; Cai, Yan; Wang, Sannan; Zhu, Meiying; Li, Jingjing; Yuan, Yunlong; Liu, Xin; Sun, Jiantong; Yang, Zuming; et al. (Frontiers in Pharmacology, 2022)
Background: Linezolid-induced thrombocytopenia (LIT) is the main factor limiting the clinical application of Linezolid(LZD). The incidence and risk factors of LIT in neonatal patients were possibly different from other populations based on pathophysiological characteristics. Our study was to establish a regression model for predicting LIT in neonatal sepsis patients. Methods: We retrospectively included 518 patients and divided them into the LIT group and non-LIT group. Logistic regression analysis was used to analyze the factors related to LIT and establish a regression model. Receiver operating characteristic (ROC) curve was drawn to evaluate the model’s predictive value. We prospectively collected 39 patients to validate the model and evaluate the effect of linezolid (LZD) pharmacokinetics on LIT. Results: Among the 518 patients, 103 patients (19.9%) developed LIT. The Kaplan–Meier plot revealed that the overall median time from the initiation of LZD treatment to the onset of LIT in premature infants was much shorter when compared with term infants [10(6, 12) vs. 13(9.75, 16.5), P=0.004]. Multiple logistic regression analysis results indicated that the independent risk factors of LIT were lower weight at medication, younger gestational ages, late-onset sepsis, necrotizing enterocolitis, mechanical ventilation, longer durations of LZD treatment, and lower baseline of platelet level. We established the above seven-variable prediction regression model and calculated the predictive probability. ROC curve showed that the predicted probability of combined body weight, gestational age, durations of LZD treatment and baseline of platelet had better sensitivity (84.4%), specificity (74.2%) and maximum AUC (AUC = 0.873). LIT occurred in 9of 39 patients (23.1%), the accuracy of positive and negative prediction of LIT were 88.9% and 76.7%, respectively. Compared with the non-LIT patients, the LIT patients had higher trough concentration [11.49 (6.86, 15.13) vs 5.51 (2.80, 11.61) mg/L; p = 0.028], but lower Vd [0.778 (0.687, 1.421) vs 1.322 (1.099, 1.610) L; p = 0.010]. Conclusion: The incidence of LIT was high in neonatal sepsis patients, especially in premature infants. LIT occurred earlier in premature infants than in term infants. The regression model had high predictive value for predicting LIT. LIT was correlated with higher trough concentration and lower Vd of LZD.